Describing the Body Shape of Rainbow Sardine (Dussumieria Acuta) Using Landmark-Based Geometric Morphometric Analysis - Luceño, Aprille Joy M.; Demayo, Cesar G. (Journal of Informatics and Mathematical Sciences, 2017)
This study utilized geometric morphometric analysis of the body shape between sexes of Dussumieria acuta. Canonical Variate Analysis (CVA) and Discriminant Function Analysis (DFA) of the relative warp scores show significant differences in the body shape between males and females. Females exhibit body shapes that are geared to support larger number of eggs as shown by the distension of their belly region and a broader body compared to the males which possess a slender body shape. Variations observed within sexes can be attributed to selection pressures present in the environment. It is concluded that landmark-based geometric morphometric analysis is a useful tool in describing variations within and between sexes of D. acuta.